The Effectiveness of Reality Therapy-Based Parenting Styles Training on Realism, Stress Tolerance and Self-Esteem of Anxious Mothers of Adolescents - Mohammad Yousefi, Sekineh; Abbasi, Ghodratollah; Emadian, Seyedeh Olia (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Anxiety is one of the issues that humans have always been involved with over time and research suggests that 20 to 65 percent of mothers suffer from depression and anxiety. The aim of this study was to determinethe effectiveness of reality therapy-based parenting styles training on realism, stress tolerance and self-esteem of anxious mothers of adolescents. Materials and Methods:The present study was an applied and semi-experimental study with pre-test and post-test with control group. The statistical population of this study included all mothers with children aged 11-16 years in Babol in the first quarter of 2019. The sample consisted of 50 mothers with children aged 11-16 years in Babol who were selected by convenience sampling method and were assigned to two groups of teaching reality therapy parenting methods (25) and control group (25 persons) using cluster sampling method. Data were collected using anxiety questionnaire, realism and stress tolerance scale and self-esteem questionnaire. Data were analyzed using multivariate analysis of covariance and SPSS.22 software. Results:The results showed that teaching reality therapy-based parenting methods was effective on realism, stress tolerance and self-esteem of anxious mothers (P<0.001). Conclusion:It can be said that teaching parenting styles based on reality therapy emphasizes on creating and maintaining a good, intimate and satisfactory relationship between parents and children by applying relationship-linking behaviors and refraining from destructive behaviors of relationships.